Encyclopedia of estate planning - Holzman, Robert S. (Boardroom Classics, 1995)
The goal of the Encyclopedia of Estate Planning is to explain in plain language the difficult concepts involved in forging an effective estate plan. The complexity of the Economic Growth and Tax Relief Reconciliation Act, signed into law makes estate planning now more important than ever. This guide seeks to help the reader master the basic tools of estate planning through clear prose and 56 chapter topics. It is meant to be a resource book for everyone, not just the wealthy. Further, regardless of what Congress does in the future to remedy the confusion associated with the new tax law, this text will still have relevance for you.